UPAYA PEMERINTAH KABUPATEN KAMPAR DALAM PEMBERDAYAAN UMKM BATIK SRIKANDI DI DESA SIBUAK KABUPATEN KAMPAR - Halimah Tussakdiah; Tito Handoko (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
The underdevelopment of micro, small and medium enterprises tends to be misunderstood by various parties. One of the problems that has caused the underdevelopment of small businesses so far is the government which substantially does not want to be serious in carrying out a strong to protect and side with the interests of small businesses. In this case, the role of the government is needed which is marked by the existence of law No.9 of 1995 concerning small business as the backbone and strengthening the structure of the national economy. In reality, there are still various kinds of problems faced by number of business actors in Kampar District, the number of which are quite large and still need to get encouragement and guidance, other problems that arise are the low quality of UMKM human resources, and the development of UMKM in Kampar district is still not optimal. Local governments have a strong enough role in advancing and developing small businesses in their regions. So this needs to be analyzed further regarding the efforts of the Kampar district government in empowering UMKM. The method used in this research is a descriptive method with a qualitative research type. The types of data in this research are primary data and secondary data. The data analysis technique used is descriptive qualitative data analysis.The results of this study are several efforts from the Kampar district government in empowering srikandi batik UMKM in sibuak village, Kampar district. Including the implementation of entrepreneurship training which is held in order to improve the ability of UMKM actors in managing their UMKM businesses. Based on several related indicators in empowering UMKM, it can be concluded that the Kampar district government through the trade department, cooperatives and UMK has tried to maximize the empowerment of UMKM in accordance with good indicators, but in the rality it is still considered less than optimal due to the lack of public knowledge and also the limited scope that is far from the reach of the government so that is not comprehensive. Keywords : Empowerment and development, UMKM